The Absence of the Transcription Factor Yrr1p, Identified from Comparative Genome Profiling, Increased Vanillin Tolerance Due to Enhancements of ABC Transporters Expressing, rRNA Processing and Ribosome Biogenesis in Saccharomyces cerevisiae - Wang, Xinning; Liang, Zhenzhen; Hou, Jin; Shen, Yu; Bao, Xiaoming (Frontiers in Microbiology, 2017)
Enhancing the tolerance of Saccharomyces cerevisiae to inhibitors derived from lignocellulose is conducive to producing biofuel and chemicals using abundant lignocellulosic materials. Vanillin is a major type of phenolic inhibitor in lignocellulose hydrolysates for S.cerevisiae. In the present work, the factors beneficial to vanillin resistance in yeast were identified from the vanillin-resistant strain EMV-8, which was derived from strain NAN-27 by adaptive evolution. We found 450 SNPs and 44 genes with InDels in the vanillin-tolerant strain EMV-8 by comparing the genome sequences of EMV-8 and NAN-27. To investigate the effects of InDels, InDels were deleted in BY4741, respectively. We demonstrated that the deletion of YRR1 improved vanillin tolerance of strain. In the presence of 6 mM vanillin, deleting YRR1 increase the maximum specific growth rate and the vanillin consumption rate by 142% and 51%, respectively. The subsequent transcriptome analysis revealed that deleting YRR1 resulted in changed expression of over 200 genes in the presence of 5 mM vanillin. The most marked changes were the significant up-regulation of the dehydrogenase ADH7, several ATP-binding cassette (ABC) transporters, and dozens of genes involved in ribosome biogenesis and rRNA processing. Coincidently, the crude enzyme solution of BY4741(yrr1Δ) exhibited higher NADPH-dependent vanillin reduction activity than control. In addition, overexpressing the ABC transporter genes PDR5, YOR1 and SNQ2, as well as the RNA helicase gene DBP2, increased the vanillin tolerance of strain. Interestingly, unlike the marked changes we mentioned above, under vanillin-free conditions, there are only limited transcriptional differences between wildtype and yrr1Δ. This indicated that vanillin might act as an effector in Yrr1p-related regulatory processes. The new findings of the relationship between YRR1 and vanillin tolerance, as well as the contribution of rRNA processing and ribosome biogenesis to enhancing S. cerevisiae vanillin tolerance, provide novel targets for genetic engineering manipulation to improve microbes’ tolerance to lignocellulose hydrolysate.